Kinesio taping - a healing and supportive method in various fields of medicine, dentistry, sport and physiotherapy - ALEKSANDRA JARON; BERENIKA KONKOL; EWA GABRYSZ-TRYBEK; JOANNA BLADOWSKA; ANNA GRZYWACZ; ARMIN NEDJAT; GRZEGORZ TRYBEK (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2021)
Kinesio taping (KT) is a method of elastic taping, created in the 1970s by a Japanese chiropractor, Dr. Kenzo Kase. The aim of this study was to present KT techniques and its application in various fields of medicine, sports and rehabilitation. The publications used in this paper were sourced from the PubMed and the Google Scholar databases. The keywords used to search databases included KT, Kinesio taping, medicine, dentistry and sport. Based on this study, it can be concluded that KT is the most recommendable method. Its use is being increasingly popular in many fields of medicine. It can be considered as an alternative for painkillers, especially in patients for whom the use of painkillers is not advisable or ineffective due to their condition. KT is well tolerated by patients and saves time; therefore, its use should be taken into account in various medical environments. In order to use this method, one should complete specialized courses, which, on the one hand, provide theoretical basis for its use, and on the other hand, teach how to choose original tapes in a practical way, as well as apply appropriate techniques in order to observe and compare the effects of one's work - therapy and treatment.